The Influences of Product Quality, Store Atmosphere and Membership Reward on Customer Loyalty of Kopi Kenangan In Manado City Through Customer Satisfaction as a Mediating Variable (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This research aims to determine the influence of product quality, store atmosphere, and membership rewards from consumers of memorable coffee on the level of customer loyalty through customer satisfaction as a mediator. The type of research used is descriptive research to describe or explain the relationship between variables using a quantitative approach. The sample taken for this research was 100 respondents. Samples were taken using nonprobability sampling technique and purposive sampling technique. The data collection instrument was a questionnaire administered via Google Form. Next, statistical testing uses SPSS Ver software. 29. The results of this research show the influence of product quality, store atmosphere, and membership rewards on customer satisfaction. Store atmosphere and membership rewards also have an influence on customer loyalty, while product quality has no influence on customer loyalty. The next result, through the mediating variable, is that product quality influences customer loyalty through customer satisfaction. The different results are that store atmosphere and membership rewards have no influence on customer loyalty through customer satisfaction.